The Competitiveness of China in the 21st Century : Analysing China's Human Capital - Dvořáková, Markéta; Stuchlíková, Zuzana, 1979-; Hnát, Pavel, 1981-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
The diploma thesis aims to discourse how China´s competitiveness has developed in the 21st century, with a special focus on human capital as one of the key factors of production that greatly fosters competitive advantage. The first chapter builds up a theoretical framework for the research part of the thesis. It reviews the concepts of competitiveness, Michael Porter´s diamond, and the theory of human capital. The second chapter examines trends and challenges of China´s competitive advantage according to Michael Porter´s diamond model. The third chapter evaluates the development of China´s human capital, its cultivation, current state, and surveys the generation Y´s attitudes to human capital.
Vedoucí práce: Zuzana Stuchlíková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses